Pengembangan WEB Comic Fantasi Cerita Sura dan Baya untuk Mengurangi Tindakan Rasisme Remaja Kota Surabaya - Nasrullah, Yusuf; Sumarwahyudi, Sumarwahyudi; Prasetyo, Abdul Rahman (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2023)
One negative impact in teenage friendship is the appearance of racial motive bullying. As we know, Indonesia is a country with thousands of cultures. Likewise in Surabaya, it was recorded several times that this activity happened in the middle of the beautiful teenage friendship. Therefore, a developed product formed as a fantasy web comic which is published in an online publisher and not be printed entitled "Kweira and the Story of the Legend Sura and Baya" aims to analyzing, developing, and communicating anti-racism insights to Surabayan teenagers so that such actions can be reduced in quantity and potential. This research use ADDIE development model which includes stages: Analysis, Design, Development, Implementation, and Evaluation. In addition validation tests by media experts and material experts done also to assess the feasibility of the product. So the result is found that fantasy web comic is usable as anti-racism counseling media for Surabayan teenagers.